PowerPoint 2013 for dummies - Lowe, Doug, 1959- (--For dummies., 2013)
Introduces the features of the newest version of PowerPoint, including adding video and animation, using a laser pointer in a presention, drawing on slides, presenting online, and collaborating with others via SkyDrive.